The Effect Of Product Quality, Price And Location On Purchase Decisions At Berkah Building Shop Lempur Danau Village, Kerinci - Edia Satria (JUMANJI (JURNAL MANAJEMEN JAMBI), 2020)
This study aims to determine: 1. Is there an effect of Product Quality on purchasing decisions at the Berkah Bangunan store and how much is the effect partially? 2. Is there a price effect on purchasing decisions at the Berkah Bangunan store and how much is the partial effect? 3. Is there any influence of location on purchasing decisions at the Berkah Bangunan store and how big is the partial effect? 4. Is there any influence of Product Quality, Price and Location on purchasing decisions at the Berkah Bangunan store and how big is the effect simultaneously? The research methodology used is descriptive qualitative and descriptive quantitative approaches. The research results are; 1. Partially there is an influence between product quality on purchasing decisions at the blessing shop in Lempur Danau Village, Kerinci Regency, as evidenced by the tcount value greater than the ttable value, and the magnitude of the effect is 17.29%. 2. Partially there is an influence between price on purchasing decisions at the blessing shop building in Lempur Danau Village, Kerinci Regency, as evidenced by the tcount value greater than the ttable value, and the magnitude of the effect is 17.55%. 3. Partially there is no influence between location on purchasing decisions at the blessing shop building in Lempur Danau Village, Kerinci Regency, as evidenced by the tcount value less than ttable value, and the magnitude of the effect is -1.21%. 4. Simultaneously there is an effect of product quality, price and location on purchasing decisions at the blessing shop building in Lempur Danau Village, Kerinci Regency, and the magnitude of the effect is 33.7%.